Raw physical properties measured on sediment core GeoB22304-5 - Lenz, Kai-Frederik; Campbell, Calvin; Gebhardt, Andrea Catalina (PANGAEA, 2025)
Sound knowledge about the petrophysical characteristics of a sediment core is a prerequisite for any subsequent paleoenvironmental study relying on sediment proxies. Physical properties of whole-round sediment cores are acquired as a first step of sediment core description, prior to slicing of sediment cores into two halves. Here, we present raw physical-properties data of core GeoB22304-5 acquired with a Geotek MSCL-S system on the unsplit core, retrieved during RV Maria S. Merian expedition MSM66 WESTBAFF to the Baffin Bay, Canada/Greenland, in 2017.
Keywords: Geotek; MSCL; Petrophysics; Physical properties; Sediment physics